Policy Options for Supporting and Restructuring Firms Hit by the COVID-19 Crisis - Araujo, Juliana (Departmental Papers; Departmental Paper, 2022)
This paper presents principles that could guide the design of more targeted policy support and facilitate the restructuring of firms adversely impacted by the COVID-19 pandemic. To this end, the paper takes stock of vulnerabilities and risks in the enterprise sector and assesses countries' preparedness to handle a large-scale restructuring of businesses. Crisis preparedness of insolvency systems is measured according to a newly designed indicator that includes five dimensions of the insolvency and restructuring regime (out-of-court restructuring, hybrid restructuring, reorganization, liquidation, and the institutional framework). Vulnerabilities tend to be more pronounced in jurisdictions with shortcomings in crisis preparedness, and those countries need to step up efforts to improve their insolvency systems.